Internet of things sensors network for outdoor environmental quality monitoring (IOT-OEQM) - Wong, Johnson Teng Fung (Nanyang Technological University, 2023)
Weather Stations or Environmental Monitoring Stations are currently used to collect weather and Outdoor Environment Quality (OEQ) information. However those stations are typically rigid, bulky, and expensive to implement to some critical locations over a vast space and have limited area coverage to collect sufficient data to cover the local variations. Outdoor Environmental Quality Monitoring Systems (OEQMS) play a crucial role in the ability to maintain healthy outdoor air quality via providing data to enforcement agencies, and there is very much a need to expand area coverage of monitoring outdoor air quality. In recent years, there has been improvements made in availability of low power of Internet-of-Things (IoT) microcontrollers with multiple wireless communication protocols, as well as the availability of low cost smart compact sensors with low power consumption and reasonable accuracy. This has made the development of smart sensor networks with standalone IoT-based OEQM modules/stations for large scale long-term OEQM more feasible. The aim of this project is to develop a low cost standalone IoT-based OEQM station or module with sufficient accuracy and reliability, suitable for large-scale long-term deployment to collect continuous environmental parameters over a large area for a long duration. With the Argon IoT microcontroller from Particle Industries Inc., a selection of commercially-available compact environmental sensor modules was chosen to interface with it to capture parameters that include temperature, humidity and particulate matter before wirelessly communicating the measurements through OEQMS Network.